A dynamic ice-structure interaction model for ice-induced vibrations by using van der pol equation. (1st December 2016) - Ji, Xu; Oterkus, Erkan
Abstract: A dynamic single degree-of-freedom ice-structure interaction model is developed based on a novel physical mechanism combination between self-excited vibration and forced vibration. Van der Pol equation, together with ice stress-strain rate curve and ice-velocity failure length are coupled to model the internal fluctuating nature of ice force in conjunction with the relative velocity caused by the structure as an external effect. Three distinct structural responses, quasi-static, steady-static and random modes have been captured during ice-structure interaction. And the key behaviour, ice force frequency lock-in phenomenon during ice-induced vibrations (IIV) is also observed. General results show good agreement with those in full-scale and small-scale experiments as well as in numerical models. Highlights: A dynamic single degree-of-freedom ice-structure interaction model is developed. The model is based on a novel physical mechanism combination of self-excited vibration and forced vibration. Van der Pol equation is coupled with ice stress-strain rate curve and ice-velocity failure length. Quasi-static, steady-static and random modes have been captured during ice-structure interaction. Ice force frequency lock-in phenomenon during ice-induced vibrations is observed.